Students’ Perception on the Utilization of BeeSpeaker Application in Speaking Class - Adelia Divany; Benni Ichsanda Rahman HZ (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examined the students’ perception on the utilization of BeeSpeaker application in improving intermediate EFL students' speaking skills at Junior High School in North Sumatera. Using case study with 30 students, data was collected through interviews, questionnaire, then analyzed using Braun and Clarke's thematic analysis framework. Five key themes emerged: enhanced pronunciation through AI feedback, increased speaking confidence, improved learner autonomy, personalized learning experiences, and sustained motivation via gamification. Results showed that the majority of students strongly believed the app helped them with pronunciation, vocabulary, fluency, and confidence. In addition, BeeSpeaker provided them with repeated opportunities for practice, immediate corrective feedback, and a safe space to overcome speaking anxiety. Thematic analysis further highlighted five core areas of improvement—better pronunciation accuracy, stronger self-confidence, wider vocabulary mastery, lower levels of speaking anxiety, and the app’s role as a supportive supplement to classroom learning. Together, these findings provide solid evidence that BeeSpeaker is not only useful but also highly effective in enhancing language learning outcomes.